Cyclin D1‐induced proliferation is independent of beta‐catenin in Head and Neck Cancer. (4th June 2013) - Sales, KU; Giudice, FS; Castilho, RM; Salles, FT; Squarize, CH; Abrahao, AC; Pinto, DS
<x xml:space="preserve">Abstract</x> Objective Head and neck squamous cell carcinoma (HNSCC) progression and metastasis have previously been associated with the activation of phosphatidylinositol 3‐kinase‐protein kinase B (PI3K‐Akt) and Wnt signalling pathways, which lead to the activation of pro‐proliferative genes, such as cyclin D1. The current study aims to investigate whether there is a crosstalk between these pathways in HNSCC and which pathway is more likely to regulate cyclin D1. Material and Methods Two HNSCC and a control keratinocyte cell lines were treated with EGF and wortmannin to respectively activate and block the PI3K‐Akt and Wnt pathways. Partial and total levels of cyclin D1, beta‐catenin and Akt were evaluated by Western blotting and immunofluorescence. Twenty‐four paraffin‐embedded samples of human HNSCC, as well as normal oral mucosa biopsies, were also immunohistochemically evaluated for beta‐catenin and cyclin D1 expression. Results Following both treatments, change in cyclin D1 protein was correlated with Akt levels only. Cytoplasmic staining for beta‐catenin and loss of its membranous expression in the HNSCC invasive areas were found in 92% of the HNSCC biopsies. Conclusion Taken together, we show that the change in cyclin D1 levels is more likely to be due to the EGFR‐Akt pathway activation than due to beta‐catenin nuclear translocation.